Pengaruh Digital Marketing, E-Word of Mouth, dan Electronic Trust terhadap Keputusan Pembelian pada Marketplace Shopee - Efendi, Mukhtar (ARZUSIN, 2024)
The aim of this research is to determine the influence of digital amrketing, e-word of mouth, and electronic trust on purchasing decisions. This research uses quantitative research with hypothesis testing. The population of this research is the marketplace shopee in Sidoarjo. The sampling technique in this study used a simple random sampling technique using the Slovin formula, so that the sample for this study was 92 people. The analysis tool used in this research uses IBM SPSS Version 25 for Windows software. The results of this research prove that digital marketing, e- word of mouth and electronic trust is a parcial influences purchasing decisions.